2020
DOI: 10.7759/cureus.10966
|View full text |Cite
|
Sign up to set email alerts
|

Severe Sepsis With Septic Shock as a Consequence of a Severe Community-Acquired Pneumonia Resulting From a Combined Legionella pneumophila and Streptococcus pneumoniae Infection

Abstract: Community-acquired pneumonia (CAP) is a frequent cause of intensive care unit (ICU) admission in adults and the sixth leading cause of death worldwide. Although co-infections have been previously reported, the co-existence of Streptococcus pneumoniae and Legionella pneumophila is exceedingly rare. Despite the fact that Streptococcus pneumoniae is the most common etiology in the majority of cases, atypical organisms such as Legione… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…In terms of prognosis, 72 patients (87.80%) exhibited a gradual recovery from the infection, while 10 patients (12.20%) succumbed to multiorgan failure (14,36,(39)(40)(41)(42)(43)(44), the majority of whom presented severe comorbid underlying conditions such as cardiovascular diseases, neoplasms, and immune-related diseases. This underscores the imperative need for heightened vigilance regarding P. micra infection, particularly in individuals predisposed to compromised oral hygiene, diabetes mellitus, malignancy, and cardiovascular and cerebrovascular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of prognosis, 72 patients (87.80%) exhibited a gradual recovery from the infection, while 10 patients (12.20%) succumbed to multiorgan failure (14,36,(39)(40)(41)(42)(43)(44), the majority of whom presented severe comorbid underlying conditions such as cardiovascular diseases, neoplasms, and immune-related diseases. This underscores the imperative need for heightened vigilance regarding P. micra infection, particularly in individuals predisposed to compromised oral hygiene, diabetes mellitus, malignancy, and cardiovascular and cerebrovascular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In this report, our patients presented with HAP and septic shock resulting from L. pneumophila. Review the literature, extrapulmonary ndings involved sepsis and septic shock are few in adults [19][20][21][22] . The clinical data of patients with sepsis and septic shock related to L. pneumophila are depicted in Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…Legionella spp. combined with other microorganisms, such as Streptococcus pneumoniae , Helicobacter cinaedi [ 96 , 97 ], and viral infections such as SARS CoV-2 [ 40 ], causes severe infection and sepsis. Interestingly, Sanchez et al recently reported co-infections of Legionella pneumophila serogroup 1 with methicillin-resistant Staphylococcus aureus (MRSA) in a COVID-19 patient.…”
Section: Clinical Manifestationmentioning
confidence: 99%